Reinventing industrial strategy : the role of government policy in building industrial competitiveness - Lall, Sanjaya (UN New YorkUS, 2004)
Reviews the nature of current globalization and evidence on the growing divergence in competitive performance in the developing world. Considers strategies adopted by the Asian Tigers to build industrial competitiveness, pointing out the pervasiveness of selective interventions and significant strategic differences between them. Concludes with lessons for other developing countries.